Transient hyperphosphatasemia in pediatric renal transplant patients--is there a need for concern and when? - Kutílek, Stěpán; Skálová, Sylva; Vethamuthu, Jennifer; Geier, Pavel; Feber, Janusz (Pediatric transplantation, 2012)
TH of infancy and early childhood is characterized by transiently increased S-ALP, predominantly its bone or liver isoforms. There are neither signs of metabolic bone disease or hepatopathy corresponding to the increased S-ALP, nor a common underlying/triggering disease. TH may also occur in children post-renal Tx, which may raise significant concerns and anxiety. We describe four patients aged 2.8-7 yr in whom the TH occurred at 11-34 (median = 28) months after Tx and lasted from 40 to 105 (median = 63) days. No obvious cause/trigger of TH could be found; the clinical status and bone turnover were not altered. In cases of TH post-Tx, we recommend the evaluation of basic biochemical indices and wrist X-ray. If these results are normal, TH is most likely the diagnosis and the S-ALP can be monitored over the next three months without further testing. In patients with persisting TH for more than three months and/or in children with pre-existing or suspected metabolic bone disease, further evaluation may be indicated. In conclusion, TH is a benign disorder in patients post-Tx. Detailed investigation including bone biopsy is only indicated in patients with persisting TH.
Keywords: Protein Isoforms; alkalická fosfatasa; Renal Insufficiency; transplantace ledvin; Radiography; výsledek terapie; Bone and Bones; mužské pohlaví; Biopsy; zápěstí; Alkaline Phosphatase; Wrist; dítě; Child; hyperfosfatemie; Child, Preschool; kosti a kostní tkáň; ženské pohlaví; radiografie; Kidney Transplantation; nefrotický syndrom; předškolní dítě; protein - isoformy; Humans; Nephrotic Syndrome; biopsie; Hyperphosphatemia; Female; Treatment Outcome; renální insuficience; lidé; Male